Childhood trauma, depression, and sleep quality and their association with psychotic symptoms and suicidality in schizophrenia. (December 2017) - Kilicaslan, Esin Evren; Esen, Asli Tugba; Kasal, Meltem Izci; Ozelci, Erdal; Boysan, Murat; Gulec, Mustafa
Abstract: This study involved the examination of the relationship between childhood trauma and both psychotic symptoms and suicidality in patients with schizophrenia after controlling for the possible confounding factors, such as clinical features, depression, and sleep quality. The Childhood Trauma Questionnaire-Short Form, Positive and Negative Syndrome Scale (PANSS), Calgary Depression Scale for Schizophrenia (CDSS), Pittsburgh Sleep Quality Index (PSQI), and the suicidality subscale of Mini-International Neuropsychiatric Interview (MINI) were administered to 199 patients with schizophrenia. We used sequential multiple stepwise regression analyses in which positive symptoms, negative symptoms, overall psychopathology, total symptoms of schizophrenia, and suicidality were dependent variables. Depressive symptomatology and childhood physical abuse significantly contributed to positive, negative, general psychopathology, and global schizophrenia symptomatology. Interestingly, general psychopathology scores were negatively associated with childhood physical neglect. Also, subjective sleep quality significantly contributed to positive schizophrenia symptoms. Although prior suicide attempts and depression were significant antecedents of suicidal ideation, no association between suicidality and both childhood trauma and sleep was found. Childhood physical abuse could have an impact on psychopathology in schizophrenia. In addition to childhood trauma, depression, sleep disturbances, and clinical features should be considered and inquired about in the course of clinical care of schizophrenia patients. Highlights: Childhood physical abuse could have an impact on psychopathology in schizophrenia. Childhood trauma, depression, sleep disturbances should be considered in schizophrenia. Psychosocial treatments should be offered to schizophrenia patients who had childhood trauma.